A bimodal pattern of the onset of COVID-19 related acute pancreatitis supports both the cytotoxic and immune-related pathogenesis - a systematic review - Bircakova, Bianka; Bruha, Radan; Lambert, Lukas; Grusova, Gabriela; Michalek, Pavel; Burgetova, Andrea (Scandinavian journal of gastroenterology, 2021)
OBJECTIVES: To review clinical and laboratory findings in patients with SARS-Cov-2 (COVID-19) related acute pancreatitis. METHODS: This systematic review was based on a database search for articles of COVID-19 related acute pancreatitis in adult patients with confirmed COVID-19 infection that included age, gender, presenting symptoms, the onset of symptoms, laboratory values, imaging findings and exclusion of common causes of pancreatitis. RESULTS: Altogether 35 articles comprising 37 patients were included. Acute pancreatitis was the first presentation of COVID-19 in 43% of patients, concurrent with general or respiratory symptoms in 14% of patients or delayed after general or pulmonary symptoms by an average of 10 ± 5 d (range, 1 - 19 d) in 43% of patients. Serum amylase and lipase levels were elevated in 87% and 100% of patients. In 50% and 84%, amylase and lipase levels exceeded three-fold the upper normal limit. Pancreatic necrosis was reported in 6% of patients and in 12% of patients, the pancreas appeared normal. Three patients died. CONCLUSIONS: We conclude that the bi-modal pattern of the onset of symptoms supports both the cytotoxic and the immune-related pathogenesis of the pancreatic injury. Acute pancreatitis may be the first symptom of COVID-19 infection. Necrosis of the pancreas is rare.
Keywords: pankreas; počítačová rentgenová tomografie; Lipase; Pancreas; pankreatitida; Amylases; Adult; dospělí; COVID-19; Pancreatitis; Humans; SARS-CoV-2; Acute Disease; lidé; lipasa; Tomography, X-Ray Computed; akutní nemoc; amylasy